PENGEMBANGAN KENDARAAN ANGKUTAN BARANG MURAH PERDESAAN - Widjajanti, Endang; Kusmaryono, Ismono; Karyawan, Karyawan (FSTPT Indonesia, 2015)
The directive of President about “Program Pro Rakyat Klaster IV should be followed with the development of low cost vehicles to enhance economic activities in the rural area, agricultural sector, and small scale industries. Low cost rural transport policy implementation give positively impact, those are can absorbs domestic components, goods distribution, rural people movements and enhance the rural economy. This paper discusses the development of low cost goods vehicles in order to support of the presidential policy. The result of the study is the development of the specifications of the rural goods vehicles.